2014
DOI: 10.1038/ncomms4427
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of TrkB signalling in CCK neurons results in hypercortisolism and obesity

Abstract: Dysregulation of hypothalamic-pituitary-adrenal (HPA) axis activity leads to debilitating neuroendocrine or metabolic disorders such as Cushing's syndrome (CS). Glucocorticoids control HPA axis activity through negative feedback to the pituitary gland and the central nervous system (CNS). However, the cellular mechanisms involved are poorly understood, particularly in the CNS. Here we show that, in mice, selective loss of TrkB signalling in cholecystokinin (CCK)-GABAergic neurons induces glucocorticoid resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…CCK is also co-localized with sleep-promoting preoptic neurons in the hypothalamus [36], which may relate to fatigue and unrefreshing sleep symptoms in ME/CFS. Finally, recent evidence suggests that CCK has a role regulating the differentiation of CD4+ T-cells [37], and that CCK-expressing neurons are a critical cellular component of the hypothalamic-pituitary-adrenal axis [38]. These roles of CCK in components of the immune system are consistent with suggested immune dysregulation in ME/CFS [8,9,[11][12][13][14][15].…”
Section: Characterisation Of Snp Rs11712777supporting
confidence: 55%
“…CCK is also co-localized with sleep-promoting preoptic neurons in the hypothalamus [36], which may relate to fatigue and unrefreshing sleep symptoms in ME/CFS. Finally, recent evidence suggests that CCK has a role regulating the differentiation of CD4+ T-cells [37], and that CCK-expressing neurons are a critical cellular component of the hypothalamic-pituitary-adrenal axis [38]. These roles of CCK in components of the immune system are consistent with suggested immune dysregulation in ME/CFS [8,9,[11][12][13][14][15].…”
Section: Characterisation Of Snp Rs11712777supporting
confidence: 55%
“…Because pyramidal cells in the CA1 area can express low levels of CCK and Cre , light‐evoked ChR2 currents could mask synaptic EPSCs in these experiments (Geibel et al, ). We therefore washed in glutamate receptor blockers NBQX (25 µM) and DL ‐APV (100 µM) at the end to measure ChR2‐contribution to light stimulation‐evoked excitatory currents.…”
Section: Resultsmentioning
confidence: 99%
“…) and BAC‐ CCK‐ Cre tg/+ mice (Fig. ) transduced with AAV:ChR2‐eYFP (see Materials and Methods) (Geibel et al, ). We first stimulated ChR2‐expressing PV+ GABAergic interneuron axons with paired‐pulse laser light pulses (3 ms, 50 ms interval) in the CA1 area, and found that wash‐in of the agonist CGS21680 (30 nM) increased IPSC amplitude in postsynaptic interneurons to 1.35 ± 0.04 of baseline ( P < 0.001, n = 12, t ‐test) (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal ACTH level in human is closely related to development of metabolic syndrome and obesity. Cushing's syndrome caused by excess production of ACTH due to pituitary tumor, share clinical features to metabolic syndrome [24, 25]. In line with this, patients with metabolic syndrome seem to have anterior pituitary gland hyperactivity [5, 6].…”
Section: Discussionmentioning
confidence: 99%